Long term adaptation of sprinters to training mezcoycle of concentrated aerobic workouts - Sadzeviciene, R.; Poderys, J. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
Aim: The aim of the study (nine national level male sprinters take part in this study) was to evaluate the influence of training-mezocycle of concentrated aerobic workouts to various body functions of sprinters. Results and Discussion: The results obtained in this study showed that was no any significant changes in CNS (Teping-test indices) and was found a significant higher values (p<0,05) in muscle power during the first assessment, i.e. before the aerobic training-mezocycle. This indicates that the total amount of training workouts performed during the mezocycle was enough difficult, even gruelling. The dynamics of cardiovascular indices during the Rufier and jump tests shoved the increase in performance abilities of cardiovascular system after the concentrated aerobic training-mezocycle. Among these indices were heart rate, JT interval, and systolic blood pressure. Some genetic markers that are exclusively associated with elite athletes have been identified yet. One of them is in the renin-angiotensin system, which plays a key role in the regulation of cardiovascular physiology, namely ACE (angiotensin I converting enzyme) [1, 3]. There was found the differences in long-term adaptation of cardiovascular system to excessive training loads in dependence on genetic peculiarities [3]. Some of these adaptation are concerned as inevitable, i.e. myocardial hypertrophy and may lead to some limitations of cardiovascular and performance abilities [2, 3]. The results obtained in our study have showed that training-mezocycle of concentrated aerobic workouts duration of two weeks was optimal for the development of cardiovascular abilities. It has been concluded that short-term training-mezocycle of concentrated aerobic loads has a positive influence to muscular and cardiovascular adaptation of athletes. The obtained results might be interest in understanding of the more accurate relationship between type of performed training loads and peculiarities of adaptation.